Infectious dengue-1 virus entry into mosquito C6/36 cells - Acosta, Eliana Gisela (2011)
The entry of dengue virus-1 (DENV-1) strain Hawaii into mosquito C6/36 cells was analyzed using a variety of biochemical inhibitors together with electron microscopy. The treatment with ammonium chloride, chlorpromazine, dansylcadaverine and dynasore inhibited virus yields, determined by infectivity titrations, whereas nystatin and methyl-β-cyclodextrin did not have any effect. The effect of the clathrin and dynamin inhibitors on DENV-1 entry was corroborated by detection of internalized virions using immunofluorescence staining. Furthermore, electron micrographs showed the incoming virions attached to electron-dense invaginations of the plasma membrane and within coated vesicles that resembled clathrin-coated pits and vesicles, respectively. The susceptibility to clathrin and dynamin inhibitors of clinical isolates from recent outbreaks was comparable to that shown by the cell culture-adapted reference strain. Similarly, DENV-3 strain H87 and DENV-4 strain 8124 were also inhibited in the presence of ammonium chloride, chlorpromazine and dynasore, allowing conclude that the infectious entry of DENV serotypes to mosquito cells occurs by low pH-dependent clathrin-mediated endocytosis. © 2011 Elsevier B.V.